Risk factors for urinary tract infection in pediatric patients - J., Kavitha; Aravind, M. A.; Jayachandran, Ganesh; Priya, Sathiya (International Journal of Contemporary Pediatrics, 2017)
Background: Urinary tract infection (UTI) is one of the common infections occurring in children causing significant morbidity and mortality. The knowledge about the risk factors helps in the management as well as preventing the recurrence of urinary tract infection. Hence this study aims to assess the various risk factors and profile of UTI. Methods:In this prospective case control study conducted in tertiary care centre between July 2011 to August 2012, children with signs and symptoms suggestive of urinary tract infection and urine culture positive for UTI were included. Age and sex matched asymptomatic children were taken as control. Preformed questionnaire was given to each patient and the results were analysed. Results: Among the 214 cases studied, 111 boys were not circumcised constituting 86.7%. Whereas the other risk factors like recent hospitalisation, recent catheterisation, common toilet usage, cleaning perineum from back to front, constipation, usage of tight underclothing, diaper usage, worm infestation, neurological abnormality, voluntary withholding of urine, reduced water intake constitute 9.3%, 0.5%, 19.6%, 17.4%, 18.2%, 0.9%, 7.9%, 26.2%, 3.7%, 33.6% and 34.6% respectively. Conclusions: Recurrent infection was most often due to unresolved bacteriuria or persistent bacteriuria than reinfection. Signs like supra pubic tenderness and hypertension are very rare. Common organisms causing urinary tract infection in our study population are E. coli followed by Klebsiella, Proteus and Pseudomonas. The risk factors of UTI depend on socioeconomic status and cultural habits.